1976
DOI: 10.1139/z76-220
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the osmoregulatory ability of three species of leech (Hirudinoidea) and its relationship to their distribution in Alberta

Abstract: Three species of freshwater leeches, Nephelopsis obscura, Helobdella stagnalis, and Theromyzon rude, were examined to determine their osmoregulatory ability. N. obscura and H. stagnalis were able to maintain themselves hyperosmotically in media between 15.6 and 59.5 mosmol/1 and between 47 and 112.7 mosmol/1 respectively but were conformers at higher media concentrations. T. rude was found to be a regulator in both hypo- and hyper-osmotic media. The relationship between the osmoregulatory ability and the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In a study of the osmoregulatory ability of freshwater leeches, Reynoldson and Davies (1976) showed that H. stagnalis was able to maintain itself hyperosmotically in media between 47 and 112.7 mosmol/L and was a conformer at higher media concentrations, and thus could survive periods of immersion in sea water. Unfortunately the osmoregulatory abilities of H. triserialis, G. complanata, and M. fervida have not been studied but if they prove to beat least as good as that of H. stagnalis, it is clear that all four species could survive the sea passage to Anticosti Island.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of the osmoregulatory ability of freshwater leeches, Reynoldson and Davies (1976) showed that H. stagnalis was able to maintain itself hyperosmotically in media between 47 and 112.7 mosmol/L and was a conformer at higher media concentrations, and thus could survive periods of immersion in sea water. Unfortunately the osmoregulatory abilities of H. triserialis, G. complanata, and M. fervida have not been studied but if they prove to beat least as good as that of H. stagnalis, it is clear that all four species could survive the sea passage to Anticosti Island.…”
mentioning
confidence: 99%
“…Nephelopsis obscura, a widely distributed species in Canada (Davies 1973), present on the Quebec North Shore but absent from Anticosti Island can only maintain itself hyperosmotically between 15.6 and 59.5 mosmol/ L (Reynoldson and Davies 1976) witha correspondingly low survival rate in salt water. Ball and Fernando (1970) concluded on the basis of the dissimilarities between the freshwater triclad faunae of Anticosti Island, Gaspé, and the Quebec North Shore, and the similarity on Anticosti Island of the triclad distribution and amphibian introductions to the island by man in 1899 (Johansen 1924) that triclads were also introduced to Anticosti Island by man.…”
mentioning
confidence: 99%